2018
DOI: 10.1016/j.amsu.2018.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Outcome assessment of emergency laparotomies and associated factors in low resource setting. A case series

Abstract: BackgroundEmergency laparotomy is a high risk procedure which is demonstrated by high morbidity and mortality. However, the problem is tremendous in resource limited settings and there is limited data on patient outcome. We aimed to assess postoperative patient outcome after emergency laparotomy and associated factors.MethodsAn observational study was conducted in our hospital from March 11- June 30, 2015 using emergency laparotomy network tool. All consecutive surgical patients who underwent emergency laparot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The magnitude of postoperative complications according to our study was 12.5%, which is similar to the global outcome study, 11.7%, 6 and lower than an African outcome cohort study which was 18.2%. 23 The study was conducted in different parts of Ethiopia, and showed higher complication rate as compared to the current findings, which was 39.2% in Gondar teaching and referral hospital 8 and 17% in Attat general hospital, Gurage zone. 9 These discrepancies may be related to the relatively better quality of surgical care delivery and the presence of qualified health care workers at a tertiary hospital compared to primary and general hospitals in Ethiopia and others were studies comprising limited systems like post-laparotomy.…”
Section: Discussionmentioning
confidence: 37%
See 4 more Smart Citations
“…The magnitude of postoperative complications according to our study was 12.5%, which is similar to the global outcome study, 11.7%, 6 and lower than an African outcome cohort study which was 18.2%. 23 The study was conducted in different parts of Ethiopia, and showed higher complication rate as compared to the current findings, which was 39.2% in Gondar teaching and referral hospital 8 and 17% in Attat general hospital, Gurage zone. 9 These discrepancies may be related to the relatively better quality of surgical care delivery and the presence of qualified health care workers at a tertiary hospital compared to primary and general hospitals in Ethiopia and others were studies comprising limited systems like post-laparotomy.…”
Section: Discussionmentioning
confidence: 37%
“…9 These discrepancies may be related to the relatively better quality of surgical care delivery and the presence of qualified health care workers at a tertiary hospital compared to primary and general hospitals in Ethiopia and others were studies comprising limited systems like post-laparotomy. 8 The overall mortality rate following all types of surgery was 2.5%. But the magnitude of death in patients who had already developed complications was significantly higher, 20.5%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations